2014
DOI: 10.1089/mdr.2012.0264
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of ESBLs and Associated Quinolone Resistance inEscherichia coliandKlebsiella pneumoniaeIsolates from an Urban Wastewater Treatment Plant in Algeria

Abstract: The aim of the study was the characterization of extended spectrum beta-lactamases (ESBLs) and quinolone resistance in cefotaxime-resistant coliform isolates from a wastewater treatment plant (WWTP). ESBLs were detected in 19 out of 24 isolates (79%) from raw water and in 21 out of 24 isolates (87.5%) from treated water, identified as Klebsiella pneumoniae and Escherichia coli. Molecular characterization of ESBLs and quinolone resistance showed allele profiles CTX-M-15 (3), CTX-M-3 (5), CTX-M-15+qnrB1 (1), CTX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
37
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 50 publications
6
37
1
Order By: Relevance
“…ESBL production rates are specifically high in wastewater due to selective pressure and genetic exchange in sludge [22]. In this study, class 1 integrons were common among ESBL-producing isolates, which was in harmony with the findings from Algeria reported by Alouache et al [73]. CTX-M-15 was found to be the most prevalent ESBL genotype in wastewater and sewage studies in most regions worldwide including the Americas, Europe and the Middle East [74].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…ESBL production rates are specifically high in wastewater due to selective pressure and genetic exchange in sludge [22]. In this study, class 1 integrons were common among ESBL-producing isolates, which was in harmony with the findings from Algeria reported by Alouache et al [73]. CTX-M-15 was found to be the most prevalent ESBL genotype in wastewater and sewage studies in most regions worldwide including the Americas, Europe and the Middle East [74].…”
Section: Discussionsupporting
confidence: 91%
“…CTX-M-15 was found to be the most prevalent ESBL genotype in wastewater and sewage studies in most regions worldwide including the Americas, Europe and the Middle East [74]. Additionally, the CTX-M-15 was previously detected in Enterobacteriaceae recovered from seawater, rivers and effluents of wastewater treatment plants and hospitals [75], and similar to our findings, was associated with TEM-1 and/or OXA-1 [73]. Additionally, sequencing of gyrA and parC genes in this study revealed a single substitution D87V and S83T in GyrA and a single S80I or double substitutions S80I and E84V in ParC conferring resistance to fluoroquinolones [73].…”
Section: Discussionsupporting
confidence: 89%
“…These findings underscore previous results reported in literature stating that use of one of the two antibiotic classes allows a co-selection process [7,8,21]. In Algeria, PMQR genes were reported from clinical human isolates both in hospital and community and were frequently associated with bla CTX-M genes [30,35].…”
Section: Discussionsupporting
confidence: 86%
“…The CTX-M-15-type ESBL-producing E. coli ST131 clone has spread across many regions of the world (28)(29)(30)(31). Our data showed that the CTX-M-15-type comprised 84 of the strains, including some strains with a combination CTX-M-15 and TEM-1 or SHV-7.…”
Section: Discussionmentioning
confidence: 70%